ELEMENTS OF OPEN PUBLIC SPACE AT CORRIDOR SOMBAOPU STREET MAKASSAR CITY - Sriany Ersina (Teknosains, 2020)
Physical elements forming characters in the corridor Somba Opu street Makassar city such as trees/shade, diversity of buildings, street furniture, open space, accessibility, density, contrast, parking, pedestrian pathways, and pavement are still considered to be less supportive of characteristics and strengthen the identity of the corridor area the street. In this case, the physical elements still give the impression of being neglected on several corridor Somba Opu street Makassar city, besides that improper arrangement and processing of elements can also affect the convenience of visitors in shopping or users of the corridor Somba Opu street Makassar city, giving rise to responses from community groups to the physical elements in the corridor. From this background, the formulation of the problem in this study is the extent of the influence of the physical elements forming the character of the corridor Somba Opu street Makassar city, and which physical elements dominate the character formation of the corridor Somba Opu street Makassar city, according to the community response. This paper is intended to analyze and find out the physical elements that dominate the character formation of the street corridor that automatically affects the characteristics that already exist on the corridor Somba Opu Street Makassar city based on the response from the community. In this study, it is based on a quantitative and qualitative paradigm, which will compare the response of the community to the physical elements forming the street character. The method in this study was through questionnaires and interviews with community groups (shop owners, street users/visitors, and street vendors) to find out their responses to the physical elements that make up the character in the corridor Somba Opu Street Makassar city, and then obtain the data analyzed with the help of the SPSS program with discriminant techniques. The results of this study indicate the element of accessibility that dominate the formation of the corridor Somba Opu street Makassar city corridor character, according to the response from the community (shop owners, users/visitors, and street vendors).